ANALYSIS OF THE DEVELOPMENT STRATEGY OF THE PINEAPPLE CHIP BUSINESS (MEDIUM SMALL MICRO BUSINESS/ UMKM) OF BERKAT BERSAMA IN KAMPAR DISTRICT - Syahrul Gunawan; Okta Karneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims were to analyze the development of Pineapple Chip Businesses (Medium Small Micro Business and next will be written as UMKM) of Berkat Bersama in Kampar District and to know the influence factors of the business development UMKM Berkat Bersama. In its development, the Berkat Bersama business has used various strategies in order to avoid major obstacles that can hamper the progress of Pineapple Chip Business. In this research, the data was gotten of the interview using key information to get accurate information. In determining the research subject, the researcher used a purposive sampling technique. Purposive sampling means the sample is taken deliberately. It means that the researchers determine their own based on certain considerations. So, the sample was not taken randomly, but determined by the researcher. The research method was a descriptive analysis that explains the research variable description and its explanation based on the research results of data reduction, data presentation, and the conclusion. After analyzing the data, the researcher concluded that the development of Pineapple Chip Business (UMKM) Berkat Bersama was a good product. Started from the planting, management, and packaging was keep the cleanness and taste. In supporting business development in the long term, UMKM Berkat Bersama collaborates with various partners. The collaborative effort was considered as one of the supporting factors to the development of Berkat Bersama Business. Another supporting factor was community participation and availability of raw materials, and so on. The community participation had a positive influence on Pineapple Chip business. Besides that, the hinder factors were limited time and high transportation costs.Keywords: Products, Human Resources, Network Marketing